THE INFLUENCE OF EMPLOYEE TRAINING, COMPENSATION AND EMPLOYEE CREATIVITY ON INNOVATIVE BEHAVIOR - Maulana, Ramli; Wijanarko, Adrian Azhar (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The existence of companies in the era of modernization really requires innovation to be able to compete. By using innovation, companies can provide better service to consumers and add value to the products they produce. PT. Jakarta Transportation has company values which encourage creativity summarized in the tagline "BISA". The respondents selected were 100 employees of PT Transportation Jakarta. There are 30 questions were distributed to respondents. The research results stated that training had no impact on innovative behavior. This is caused by inappropriate training methods. Apart from that, compensation and employee creativity have an impact on Transjakarta's innovative behavior